THE EFFECT OF TRADE CREDIT ON COMPANY PROFITABILITY IN THE CONSUMER GOODS INDUSTRY SECTOR FOR THE PERIOD 2020-2022 - Fendy Surya Lukito; Ignatius Roni Setyawan (International Journal of Application on Economics and Business, 2024)
The purpose of this research is to determine the effect of trade credit provision on the profitability of companies in the consumer goods industry sector from 2020 to 2022 and also to determine the effect of trade credit provision at a higher level and a lower level than the average company in the primary consumer goods industry sector on company profitability. Finally, this study will determine the effect of trade credit provision on the profitability of primary consumer goods sector companies during the COVID-19 pandemic crisis. The empirical analysis method is carried out on a sample of companies listed on the Indonesia Stock Exchange during the period 2020-2022. To test the research hypothesis, panel data analysis methodology is used with moderation of accounts receivable variables, company growth, third-party debt, bank loans, accounts payable, and dummy variables. The results showed that trade credit contributed to the profitability of the companies studied. The empirical analysis also reveals that firms can improve their profitability by increasing investment in trade receivables to a higher level than firms in their business sector. In addition, greater use of debt to suppliers and increased bank debt tend to reduce the contribution of trade receivables to firm profitability.